2009
DOI: 10.1111/j.1438-8677.2009.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollination system of thePilosocereus leucocephaluscolumnar cactus (tribe Cereeae) in eastern Mexico

Abstract: It has been suggested that there is a geographic dichotomy in the pollination systems of chiropterophilous columnar cacti: in intra-tropical areas they are pollinated almost exclusively by bats, whereas in extratropical areas they are pollinated by bats, birds and bees. However, currently the studies are clumped both taxonomically (mainly Pachycereeae species) and geographically (mainly in the Tehuacan Valley and the Sonoran Desert). This clumping limits the possibility of generalising the pattern to other reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…The latter seem to be common in species inhabiting extratropical latitudes, whereas the specialized systems are characteristic of tropical species, supporting the geographic dichotomy hypothesis put forward by Fleming et al (1996) and Valiente-Banuet et al (1996). Different studies have confirmed this pattern for species occupying tropical latitudes in the northern hemisphere (Fleming 1993;Nassar et al 1997;Valiente-Banuet et al 1997a;Ibarra-Cerdeña et al 2005;Munguía-Rosas et al 2009;Arzabe et al 2017); however, research on the pollination systems in Cactaceae inhabiting tropical and subtropical regions in the southern hemisphere suggests that dependence on pollinators is not as strong, bringing about mixed mating systems (e.g. Corryocactus melanotrichus (K.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The latter seem to be common in species inhabiting extratropical latitudes, whereas the specialized systems are characteristic of tropical species, supporting the geographic dichotomy hypothesis put forward by Fleming et al (1996) and Valiente-Banuet et al (1996). Different studies have confirmed this pattern for species occupying tropical latitudes in the northern hemisphere (Fleming 1993;Nassar et al 1997;Valiente-Banuet et al 1997a;Ibarra-Cerdeña et al 2005;Munguía-Rosas et al 2009;Arzabe et al 2017); however, research on the pollination systems in Cactaceae inhabiting tropical and subtropical regions in the southern hemisphere suggests that dependence on pollinators is not as strong, bringing about mixed mating systems (e.g. Corryocactus melanotrichus (K.…”
Section: Introductionsupporting
confidence: 61%
“…; Munguía‐Rosas et al . ; Arzabe et al . ); however, research on the pollination systems in Cactaceae inhabiting tropical and subtropical regions in the southern hemisphere suggests that dependence on pollinators is not as strong, bringing about mixed mating systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has not been formally described yet, we have observed that individuals in the study area produce flowers in discrete pulses (Munguía-Rosas 2008;Munguia-Rosas et al 2009b). In light of our field observations, we suspected that flowering phenology was synchronous and pulsed, which is very rare Pattern in terms of number of flowering peaks (uni-, bi-, or multimodal), the relationship between rainfall, temperature, and plant size with the number of flowers per plant (flowers) and the onset of flowering (onset) are shown.…”
Section: Introductionmentioning
confidence: 97%
“…2003; Bustamante & Búrquez 2008; Bustamante et al. 2010; Munguía‐Rosas et al. 2010) revealed that almost all of them are self‐incompatible, the only exceptions being Polaskia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on pollination biology of 22 Mexican species of columnar cacti (Valiente-Banuet et al 1996;Cruz & Casas 2002;Otero-Arnaiz et al 2003;Bustamante & Bú rquez 2008;Bustamante et al 2010;Munguía-Rosas et al 2010) revealed that almost all of them are self-incompatible, the only exceptions being Polaskia spp. (Cruz & Casas 2002;Banuet (2002), also allows visualising a corresponding geographic pattern of vulnerability associated with specialised pollination: the populations of columnar cacti from central and southern Mexico being more vulnerable to absence or scarcity of their pollinators.…”
Section: Introductionmentioning
confidence: 99%